(untitled) (Damu Journal of Sport Sciences, 2024)
The study included four chapters, as the first chapter included the introduction and the importance of the research, and the study included an objective, which is to identify finding a proposed equation to determine the stride length of the runner. As for the second chapter, it included the research methodology, as the descriptive method was chosen to suit the nature of the study, while the research sample included those who obtained the sequence from (1-8), i.e. those who reached the final in the (100-meter) event. After presenting, analyzing and discussing the results in the third chapter, there was no significant difference between the results of the proposed equation to determine the stride length of the runner and the actual results. Chapter five included several conclusions, including the proposed equation that has an important role in determining the stride length of an effective runner (100 m). The average stride length is one of the main factors affecting achievement. Lower limb measurements and hip joints capacity are specific to the stride length of a 100 m runner. There were a set of recommendations, including the researcher recommending that trainers pay attention to the results of scientific studies to determine the important variables in achievement.